Teacher Innovation through Knowledge Management and Personality Strengthening - Sukmanasa, Elly; Novita, Lina (JURNAL AL-TANZIM, 2023)
This study aims to increase teacher innovation by examining knowledge management and personality relationships. The method used is a combination of correlation approaches and Sitorem analysis. There were 271 samples from a population of 1684 elementary school teachers with civil servant status using multistage proportional sampling. Data analysis comprised normality, homogeneity, linearity, and multiple regression tests. The study's results prove a solid or significant relationship between knowledge management and personality and teacher innovation, as indicated by the correlation coefficient ry123 = 0.652. SITOREM analysis shows that based on the order of priority, improvements that need to be increased include knowledge dissemination, awareness, openness, personal consideration, and business and organizational innovation. At the same time, the indicators that are maintained and developed are influence, product innovation, emotional stability, process innovation, inspirational motivation, application of knowledge, knowledge storage, agreeableness, service innovation, knowledge acquisition, intellectual stimulation, extraversion, and knowledge evaluating.